2010
DOI: 10.1093/jb/mvq069
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the biological clock gene Bmal1 on tumour growth and anti-cancer drug activity

Abstract: The Bmal1 gene plays a key role in controlling circadian rhythms. To better understand how the Bmal1 gene affects tumour growth and the response to anti-cancer drugs, we examined the effect of knockdown of Bmal1 by RNAi both in vitro and in vivo. Down-regulation of Bmal1 gene expression accelerated cell proliferation in vitro and promoted tumour growth in mice. Suppressing Bmal1 expression in murine colon cancer cells (C26) and fibroblast cells (L929) decreased apoptosis induced by Etoposid, reduced the distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 19 publications
6
58
1
Order By: Relevance
“…Another report showed that BMAL1-deficient fibroblasts have reduced sensitivity to the DNA damage-inducing anticancer drugs, etoposide and daunorubicin (8). Our previous study also demonstrated that Bmal1 plays a role involved in the effect of cisplatin in mice (33). In the present study, we found that Bmal1 overexpression induces G 2 -M phase arrest in HCT116 and THC8307 cell lines after oxaliplatin treatment, indicating that the DNA damage-repair signaling pathway is involved in this process.…”
Section: Discussionsupporting
confidence: 78%
“…Another report showed that BMAL1-deficient fibroblasts have reduced sensitivity to the DNA damage-inducing anticancer drugs, etoposide and daunorubicin (8). Our previous study also demonstrated that Bmal1 plays a role involved in the effect of cisplatin in mice (33). In the present study, we found that Bmal1 overexpression induces G 2 -M phase arrest in HCT116 and THC8307 cell lines after oxaliplatin treatment, indicating that the DNA damage-repair signaling pathway is involved in this process.…”
Section: Discussionsupporting
confidence: 78%
“…In a recent study, loss of BMAL1 has been shown to reduce the expression of PER1, PER2, PER3, and p53 [27]. The downregulated circadian clock gene BMAL1 also accelerates the development of tumors and may influence the response to anti-cancer drugs [27]. Therefore, it is reasonable to hypothesize that circadian clock genes can regulate or suppress other circadian gene in the certain mechanism and this may also explain why most circadian genes (PER1, PER2, PER3, CRY1, CRY2, and BMAL1) are downregulated at the same time in HNSCC.…”
Section: Discussionmentioning
confidence: 91%
“…In HNSCC, the downregulated and disrupted circadian clock genes possibly lost their function of eliminating premalignant and malignant cells, hence leading to the accumulation of malignant cells and evolution of malignancies. In a recent study, loss of BMAL1 has been shown to reduce the expression of PER1, PER2, PER3, and p53 [27]. The downregulated circadian clock gene BMAL1 also accelerates the development of tumors and may influence the response to anti-cancer drugs [27].…”
Section: Discussionmentioning
confidence: 99%
“…In support of human studies, experimental work in rodents documented accelerated tumor growth when mice, engrafted with lung adenocarcinoma or Glasgow osteosarcoma, were exposed to repeated jet lag conditions [9,10]. Similarly, enhanced tumor development has been described in mice with genetic disruption of the circadian clock (although this is not the case for all clock gene mutants) [9,[11][12][13] or surgical lesion of the central clock [14]. Taken together, circadian disruption coincides with increased carcinogenesis and faster tumor growth in a wide range of experimental setups.…”
Section: Circadian Clock Disruption Is Associated With Cancermentioning
confidence: 91%
“…In contrast to healthy cells with a cell-division rate of about 24 h, cancer cells are characterized by uncontrolled fast cell division. In fact, the literature reports that cell-cycle gene expression is altered in cancer cells [11,15] and that increased levels of the proto-oncogene Myc, upon mutation of clock genes in tumor cells, correlate with the cell-division speed [9]. Since the cell cycle is under circadian control, cancer cells might enhance their proliferation through manipulation of the circadian control over the cell cycle.…”
Section: Targeting the Clock In Tumors?mentioning
confidence: 99%